Garlic inhibitory effect on platelet activity induced by different agonists - González, Roxana Elizabeth; Soto, Verónica Carolina; Sance, María Mirta; Galmarini, Claudio Rómulo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2021)
Platelets are essential elements of human blood. In addition to their normal role, platelets are involved in causing myocardial infarction, stroke and other thrombotic disorders. Platelet activation in vivo, probably involves a combination of agonists. Garlic has beneficial effects due to its ability to inhibit platelet aggregation and thromboxane formation. The aim of this work was to evaluate the ability of garlic extracts to inhibit platelet aggregation induced by different agonists and their mixtures in different donors. Significant differences were found in platelet aggregation in response to each agonist (P â‰¤ 0.05). The highest antiaggregatory effect was observed with arachidonic acid and the lowest effect with collagen-arachidonic acid mixture. Interaction effects between donor and agonist (or mixtures) were detected. The study showed the potential of aqueous garlic extracts to prevent platelet aggregation induced by different agonist. Highlights Platelets play a central role in the progression of atherosclerotic lesions. Blood from nine non-smoker healthy donors was used for in vitro platelet aggregation study. Significant differences were found in platelet aggregation in response to each agonist. Aqueous garlic extracts could prevent platelet aggregation induced by different agonist.